Hopfield neural network computation as an alternative solution for solving economic dispatch in power system - Melaty Amirruddin, 1986-; Abdullah Asuhaimi Mohd. Zin; Fakulti Kejuruteraan Elektrik (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2010